A RSSI-Based Mesh Routing Protocol based IEEE 802.11p/WAVE for Smart Pole Networks - Choi, Jong Young; Park, Jiwoong; Lim, Sung Hwa; Ko, Young Bae (International Conference on Advanced Communication Technology, ICACT, 2022)
This paper proposes a RSSI-based routing protocol for smart pole mesh networks equipped with multiple IEEE 802.11p/WAVE radios. In the IEEE 802.11p based multi-radio multi-channel environments, the performance of traditional mesh routing protocols is severely degraded because of metric measurement overhead. The periodic probe messages for measuring the quality of each channel incurs a large overhead due to the channel switching delay. To solve such an overhead problem, we introduce a routing metric that estimates expected transmission time and proposes a light-weight channel allocation algorithm based on RSSI value only. We evaluate the performance of the proposed solution through simulation experiments with NS-3. Simulation results show that it can improve the network performance in terms of latency and throughput, compared to the legacy WCETT routing scheme.
Keywords: Channel allocation; IEEE 802.11p; Mesh routing; MeshNetworks; Multi-channel environment; Multi-radio; Performance; Routing-protocol; RSSI; Smart pole; channel allocation; IEEE 802.11p; routing protocol; RSSI; smart pole; WAVE; wireless mesh network